Internalization of Inclusive Values in Al-Islam and Muhammadiyahan Learning Activities - Munawaroh, Dina; Samsudin, Muh; Abdul Manan, Nanan; Fitriyani, Yani (Journal of Islamic Education and Ethics, 2025)
This research aims to describe the application of inclusive values ​​in Al-Islam and Muhammadiyah learning at Muhammadiyah University of Kuningan. This qualitative research or case study, namely an in-depth investigation, was carried out through a field research procedure (field research) that used descriptive data in the form of written or spoken words from people, observable behavior, and emerging phenomena. The research subjects or informants were Al-Islam and Muhammadiyah students and lecturers. The data collection technique is observation, and the data analysis uses an inductive thinking approach. The results of the research show that at the Muhammadiyah University of Kuningan, AIK learning activities have not fully implemented inclusive values, one of which is that non-Muslim students are still obliged to take part in Islamic courses and activities. Therefore, this study suggests that lecturers and students can apply inclusive values ​​through Al-Islam and Muhammadiyah learning activities so that through the introduction of religious learning, students can implement them in their daily lives, both inside and outside of the university environment.